Komunitas Kodok pada Lahan Terdegradasi di Areal Curug Nangka, Jawa Barat - Kurniati, Hellen; Sumadijaya, Alex (Perhimpunan Biologi Indonesia, 2012)
Frogs communities of degraded areas in Curug Nangka area, West Java. A Total of thirteenfrog species were found in degraded land areas of Curug Nangka, on the foot hills of MountSalak at elevation of 640 m - 730 m above sea level (asl). In the fast-flowing river habitat, threefrog species dominated this habitat, they were Huia masonii, Hylarana chalconota andOdorrana hosii; whereas in fast-flowing ditch habitat, Phrynoidis aspera and H. chalconotawere the dominant species, and for the pine plantation, H. chalconota and H. nicobariensisdominated this habitat. On the river transect, the presence of individuals H. masonii wasinfluenced by the dynamics of air temperature and water temperature. In the open ditchtransects, the presence of individual P. aspera was influenced by water temperature. Therewas a stronger positive association between the presence of individuals H. masonii andindividuals of O. hosii than between individual O. hosii and H. chalconota on the rivertransect. Among individuals of H. masonii and individuals of H. chalconota there was apositive association; however in the open ditch transects, there was no association betweenthe presence P. aspera and H. chalconota. The presence of H. chalconota and H. nicobariensison the pine plantation transect had strong positive association.Keywords: frog community, degraded area.